ELECTRONIC PORTABLE ARTICULATION MIRROR (EPAM): MEDIA UNTUK MENINGKATKAN BAHASA MIMIK ANAK TUNARUNGU - Bunyanuddin, Erbi; Nugroho, Doni Bowo; Prathamie, Rahayu Rizky; Junianto, Rizki; Nur Huda, Muhammad (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Communication is a fundamental human need to interact with each other. For children with special needs, particularly children with hearing impairment, communication becomes very important because they must to learn to communicate harder than a normal child. In SLB Karnna Manohara articulation mirror used as a device to train children with hearing impairment in communication, especially in terms of language expression. But the device is less effective because the size is large and not portable. The purpose of this program is implementation Electronic Portable Articulation Mirror (EPAM) which is a modification of a large mirror articulation into a portable, practical and more effective. Implementation of this program is done through several steps, they are observation, device improvements, feasibility test (calibration), evaluation and revision, application of device, and evaluation. The results of this program are EPAM design that consists of a mirror, an LCD display, a control menu, sound indicator light, power indicator light, power button, display baterray checker, 3.5 mm audio port, audio port 7 mm, charger port, speakers, headsets, and microphone. Then for the implementation of EPAM in speech therapy business unit of SLB Karnna Manohara has succeeded in increasing the expression of language ability of deaf children to gain (g) 0.72 and increased capacity with high criteria.Keywords : articulation portable electronic mirror, children with hearing impairment, language expression